Sudan increases wheat production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Wheat production in Sudan increased significantly in 1991/92, due to a combination of factors: favorable weather; input availability, and the Government\92s interest and investment in research and transfer of technology. Despine an 18% decrease in...